2018
DOI: 10.1038/s41387-018-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of body mass index on the incidence of diabetes and diabetic retinopathy in two Asian populations

Abstract: AimsTo examine the association of body mass index (BMI) with the incidence of diabetes mellitus (DM) and diabetic retinopathy (DR) in Asians.MethodsWe analysed data from 4101 adults (Malay, n = 1901 and Indian, n = 2200) who participated in the baseline (2004–2009) and 6-year follow-up (2011–2015) of two independent population-based studies with similar methodology in Singapore. BMI was categorised into normal (<25 kg/m2), overweight (25–29.9 kg/m2) and obese (≥30 kg/m2). DM was diagnosed as random plasma gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
2
26
1
Order By: Relevance
“…40 Sasongko et al 41 reported that high BMI was significantly associated with lower risk of DR in Indonesians with type 2 diabetes. Similarly, Chan et al 42 reported an inverse association between BMI and incidence of DR in separate prospective cohorts of Malays and Indians.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…40 Sasongko et al 41 reported that high BMI was significantly associated with lower risk of DR in Indonesians with type 2 diabetes. Similarly, Chan et al 42 reported an inverse association between BMI and incidence of DR in separate prospective cohorts of Malays and Indians.…”
Section: Discussionmentioning
confidence: 82%
“…38,39 On the contrary, several studies have shown that obesity has the potential to diminish the severity of DR in Asians with type 2 diabetes. [40][41][42] Man et al 40 pointed out that generalized obesity and abdominal obesity may have different effects on DR. Although a high waist-to-hip ratio increased the risk of DR, a high BMI decreased the risk of DR in Asians with type 2 diabetes recruited from the Singapore National Eye Centre.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms underlying the inverse association between BMI and DR are uncertain. 48 It may not be that higher BMI is protective towards DR, but that individuals with lower BMI may have more severe DM (as patients with decompensated disease may undergo a catabolic phase resulting in unintentional weight loss) and thus have a higher risk of developing DR. 48 Lu et al also attributed this inverse relationship to better pancreatic β-cell function in overweight individuals. 46 In contrast to our observation, however, studies in Turkey 23 and Australia 49 found obesity to be an independent risk factor for DR with persons with higher BMI being more likely to have DR and more severe stages of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of a lower prevalence of DR in patients with a higher BMI in this study should therefore, be interpreted with caution as overweight and obesity have been associated with many health risks including DM as well as overall mortality. 48,51,52 A limitation of this study was our inability to do optical coherence tomography and Fundus Fluorescein Angiography (FFA) due to lack of necessary equipment.…”
Section: Discussionmentioning
confidence: 99%
“…[28,30,31] Another study shows that higher body mass index was associated with a higher incidence of diabetes but a lower incidence of DR over a 6-year period in Asian Malays and Indians. [32] Among different eye diseases, obesity has been linked with age-related cataract, glaucoma, age-related maculopathy, and DR. However, the nature and strength of these associations remain to be determined.…”
Section: Association With Obesitymentioning
confidence: 99%